The Role of Gender Equality on Poverty Alleviation: Case of Indonesia - Dwi Atmi Rohmatilah (Ministry of National Development Planning Republic of Indonesia/Bappenas, 2023)
The Gender Development and Empowerment Index of Indonesia, which represents the equality between genders, has consistently fallen below the global average since 1990. This concerning trend gains significance given that half of the country's population is female. Relying on only half of the population for economic and developmental progress is suboptimal. Hence, fostering empowerment for all genders emerges as a potentially more effective strategy to catalyse economic growth and alleviate poverty across the nation. This study investigates how gender equality measures affect poverty at the regional level using dynamic panel data by system-generalised method of moments (system-GMM) technique on 514 districts in Indonesia spanning from 2014 to 2020. The result indicates that the Gender Development Index, characterized by a higher average score and lower standard deviation pronounces a more positive effect on poverty alleviation in comparison to the Gender Empowerment Measure. This can be attributed to the prevailing underrepresentation and limited participation of women in critical spheres such as the economy, higher-level management, parliamentary activities, and decision-making processes. Thus, there is a need to reinforce women's inclusion into formal positions and campaign for the participation of both genders in household chores and childcare to improve gender equality. Even small increases in the opportunities available to women and some release of cultural and political constraints can lead to significant economic and social benefits.